Development of IPAS worksheets using augmented reality to enhance critical thinking skills - Asni Defita Sari Sianipar; Retno Dwi Suyanti; Waminton Rajagukguk (Himpunan Pengembang Kurikulum Indonesia, 2025)
The use of innovative media, such as Augmented Reality (AR)-based Student Worksheets (LKPD), is a solution to improve the quality of 21st-century learning, especially in addressing the limitations of conventional media in elementary schools. AR technology enables the visualization of concepts contextually and interactively, promoting student engagement and developing critical thinking skills. This study aimed to develop an AR-based LKPD for the IPAS subject on the human digestive system for Grade 5 students. It employed a Research and Development (R&D) approach using the ADDIE model at UPT SD Negeri 067250 Medan. The subjects included Grade V students, classroom teachers, and three expert validators (subject matter, design, and language). Data were collected through expert validation sheets, practical questionnaires, observation, and documentation, and were analyzed using descriptive and quantitative techniques. Product trials were conducted in two stages: a small group (9 students) and a field trial (30 students). Validation and revision ensured the quality of content, design, language, and media display. The final product was tested for practicality and effectiveness in enhancing students’ critical thinking. The integration of AR in LKPD IPAS enhanced students’ critical thinking through interactive visuals, expert validation, and positive trial results. The developed AR-based LKPD proved to be valid, practical, effective, and aligned with the Kurikulum Merdeka and the contextual digital learning needs. Abstrak Penggunaan media inovatif seperti LKPD berbasis Augmented Reality (AR) menjadi solusi untuk meningkatkan kualitas pembelajaran abad ke-21, terutama dalam mengatasi keterbatasan media konvensional di sekolah dasar. Teknologi AR memungkinkan visualisasi konsep secara kontekstual dan interaktif sehingga mendorong keterlibatan serta kemampuan berpikir kritis peserta didik. Penelitian ini bertujuan mengembangkan LKPD IPAS berbasis AR pada materi sistem pencernaan untuk peserta didik kelas V. Penelitian ini merupakan R&D dengan model ADDIE untuk mengembangkan LKPD berbasis AR di kelas V UPT SD Negeri 067250 Medan. Subjek meliputi peserta didik kelas V, guru kelas, dan tiga validator (ahli materi, desain, dan bahasa). Data dikumpulkan melalui validasi ahli, angket kepraktisan, observasi, dan dokumentasi, lalu dianalisis secara deskriptif kuantitatif. Uji coba dilakukan dalam dua tahap: kelompok kecil (9 peserta didik) dan lapangan (30 peserta didik). Validasi dan revisi dilakukan untuk memastikan kelayakan isi, desain, bahasa, dan tampilan media. Produk akhir diuji untuk menilai kepraktisan dan efektivitasnya dalam meningkatkan kemampuan berpikir kritis peserta didik. Integrasi teknologi AR dalam LKPD IPAS meningkatkan kemampuan berpikir kritis peserta didik melalui penyajian visual interaktif, validasi ahli, serta uji kepraktisan dan efektivitas dengan hasil positif. Pengembangan LKPD IPAS berbasis AR terbukti valid, praktis, dan efektif serta sesuai dengan Kurikulum Merdeka dan kebutuhan pembelajaran digital kontekstual. Kata Kunci: Assemblr Edu; augmented reality; berpikir kritis; IPAS